Environmental Provisions in American and EU Free Trade Agreements: A Preliminary Comparison and Research Agenda. Issue 3 (November 2013) - Jinnah, Sikina; Morgera, Elisa
<x xml:space="preserve">Abstract</x> Environmental provisions are included into bilateral trade agreements in increasingly creative ways. This article offers an initial exploration of the policy and legal dimensions of environmental provisions included in recent bilateral trade agreements concluded by the United States and by the European Union. Based primarily on a coding analysis of the environmental provisions contained in American and EU trade agreements since the mid‐2000s, the article illuminates the variable characteristics of these environmental provisions, including the different approaches of the United States and the EU (punitive versus cooperative) to their implementation. The article pays particular attention to the unprecedented links that these treaties create with multilateral environmental agreements. It concludes with a discussion of avenues for future research, including approaches that are comparative and interdisciplinary in nature.